2020
DOI: 10.1097/pec.0000000000001274
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Febrile Seizures in Japanese Children With Occult Bacteremia

Abstract: Objectives Fever of 39°C or higher and a white blood cell (WBC) count of 15,000/μL or greater are known predictors of occult bacteremia (OB). However, because of a decreasing prevalence of OB, WBC counts have become poor predictors of OB in populations of routinely immunized children. Thus, we aim to evaluate the clinical characteristics of OB in Japanese children and identify potential risk factors for OB. Methods We conducted an observational study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The prevalence of OPB in patients with febrile seizures was 24–42% in the pre‐PCV era, and 28% in the post‐PCV era in the USA . Previous studies in Japan showed high prevalence rates of febrile seizures of 53% and 55% . This difference may be explained by the known higher overall prevalence of febrile seizures in Japan compared with Western countries (8.3–9.9% vs 2–5%) .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The prevalence of OPB in patients with febrile seizures was 24–42% in the pre‐PCV era, and 28% in the post‐PCV era in the USA . Previous studies in Japan showed high prevalence rates of febrile seizures of 53% and 55% . This difference may be explained by the known higher overall prevalence of febrile seizures in Japan compared with Western countries (8.3–9.9% vs 2–5%) .…”
Section: Discussionmentioning
confidence: 85%
“…7 Previous studies in Japan showed high prevalence rates of febrile seizures of 53% and 55%. 1,15,16 This difference may be explained by the known higher overall prevalence of febrile seizures in Japan compared with Western countries (8.3-9.9% vs 2-5%). [17][18][19] The reason for the relatively high rates of febrile seizures in patients with OPB is unknown, but it suggests that screening for OPB may be more effective in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations